Investigation of the relationships between life satisfaction, optimism, happiness and blood lipid, vitamin-D levels of individuals aged 55 and over (Annals of Medical Research, 2022)
Aim: This study was carried out to investigate of the relationships between life satisfaction, optimism and happiness on blood lipid and vitamin-D levels in people aged 55 and over.Materials and Methods: This cross-sectional study was conducted on 283 individuals over the age of 55. The survey consisted of two main parts. In the first part, there are 19 questions about the socio-demographic characteristics of the patients, their chronic disease status, alcohol and smoking habits, physical activity and sunbathing duration. In the second part, Life Satisfaction Scale, Life Orientation Test and Subjective Happiness Scale were used. The lipid parameters and Vitamin D levels were investigated as dependent variables. Socio-demographic characteristics of individuals, physical activity status, and average scores of scales were investigated as independent variables.Results: The results indicated that, LDL level was significantly and reverse associated with subjective happiness level. There was no significant relationship between other lipid parameters and subjective happiness level. It was determined that there was a significant and linear relationship between vitamin D level and life satisfaction and subjective happiness levels.Conclusion: Understanding the psychological characteristics and the factors affecting their psychology of individuals aged 55 and over may play a key role for a healthy population, prevention of cardiovascular diseases and low vitamin D deficiency.
Keywords: vitamin-D; optimism; serum lipid profile